MODELING SYSTEM OF ONCE THROUGH STEAM GENERATOR FOR STEAM FLOODING ENHANCED OIL RECOVERY - , SABILA ROSYADI, Dr. -Ing Sihana, Faridah, S.T., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Enhanced Oil Recovery (EOR) is an oil recovery method that involves the injection of fluid which does not originally exist in the reservoir. One of the EOR methods is steam flooding EOR that uses water vapor as the working fluid. Once Through Steam Generator (OTSG) is one of the steam generator types that is generally used on steam flooding EOR. OTSG is a steam generator without a separator between water and steam. OTSG consists of 2 processes called preheating on economizer part and evaporation on evaporator part. The modeling starts with an understanding of process in the OTSG system. It consists of mass and energy balance on the economizer and evaporator. Modeling equation composed to 4 equations: change in economizer length, change in enthalpy inside economizer, change in density inside evaporator, and change in enthalpy inside evaporator. System response indicated by a change in outlet enthalpy that comes out from OTSG. The response itself obtained from a simulation by changing a system input variable in the form of incoming enthalpy to OTSG, heat flow rate, and mass flow rate of feed water. Response characteristics was obtained from simulation. OTSG system response was obtained by approaching with the first order of dynamic modelling equation. Value of time constant is 2,772 seconds for the change in the heat flow rate of the feed water into the OTSG and 4,52 seconds for the change in the flow rate of the feed water into the OTSG. Changes in the steam quality that comes out from OTSG depend on the value of steam enthalpy that comes out from OTSG.